MÃ‰TODO DOS MÃNIMOS QUADRADOS PONDERADOS NA ANÃLISE DE GRUPO DE EXPERIMENTOS - Oliveira, Wilson Alves de; Nogueira, Maria Cristina Stolf (REVISTA DE AGRICULTURA, 2015)
MÃ‰TODO DOS MÃNIMOS QUADRADOS PONDERADOS NA ANÃLISE DE GRUPO DE EXPERIMENTOS